Generalized stochastic model of creep and creep rupture beams in pure bending and its application to the estimation of reliability - V. P. Radchenko; M. V. Shershneva; V. V. Tsvetkov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2012)
Generalized stochastic model of creep and creep rupture beams under pure bending in terms “generalized load”, “generalized displacement”, “time” is offered. Beam is considered as a single entity (the specific model). The complete analogy between the curves of uniaxial creep sample under constant stress and generalized creep curves beams in the curvature of the beam coordinates “curvature beams— time” under the constant bending moment is determined. On the basis of this analogy the stochastic equation of state beam is formed. Method of reliability estimating of the beams bending under creep on parametric criteria of failure in a significant scatter of the data is developed. Calculation results and recommendations for lifelength assigning are presented.